Reconstructing feedback in graduate medical education: development of the REFLECT scale to measure feedback delivery in medical residency training - Mehran Ilaghi; Sara Shafian; Adel Soltanizadeh; Ali Karamoozian; Maryam Okhovati; Sarah Aflatoonian (BMC Medical Education, 2023)
Abstract Background Feedback plays a pivotal role in graduate medical education, where medical residents are expected to acquire a wide range of practical and professional competencies. Assessing the feedback delivery status is a preliminary step for educators to enhance the quality of feedback provided. This study aims to develop an instrument to assess the various aspects of feedback delivery in medical residency training. Methods The fifteen-item REFLECT (Residency Education Feedback Level Evaluation in Clinical Training) questionnaire was developed. The content validity was evaluated according to a panel member consisting of fourteen clinical professors and medical education instructors. After evaluating the test-retest reliability, the questionnaire was distributed to a sample of 154 medical residents and was further assessed in terms of internal consistency and factor analysis. Results Content validity analysis resulted in an appropriate content validity ratio and content validity index for the final 15 items. The test-retest reliability resulted in an ICC of 0.949 (95% C.I. 0.870–0.980), indicating excellent reliability. The Cronbach’s alpha for the 15-item questionnaire was α = 0.85, demonstrating good internal consistency. The factor analysis resulted in a four-factor structure: “attitude towards feedback”, “quality of feedback”, “perceived importance of feedback”, and “reaction to feedback”. Conclusions REFLECT proved to a reliable tool that could be utilized as a quick assessment method of feedback delivery, making it a suitable aid for educational managers and faculties to design necessary interventions aiming to enhance the quantity and quality of feedback provided.